Comparing the effects of semantically related and non-related verb retrieval treatments in persons with aphasia: a single-case study - Mamani, Faezeh; Yadegari, Fariba; Sazegar Nejad, Samaneh (Aphasiology, 2023)
Differential topographies of body limbs in the brain would be reflected in differential associations of body-related action verbs. This neuroscience hypothesis may have important implications for the verb dissociations in persons with agrammatic aphasia. This study aimed at examining the effects of semantic feature analysis (SFA) on verb retrieval with an innovation based on the theory of the topographical representation of the verb-semantic functional units through distributed neural circuits. The research question concerned the effect of a verb-oriented SFA approach on two sets of semantically related and non-related verbs for Persian-speaking persons with aphasia. Two versions of SFA were applied through a single-subject crossover study with A 1 B 1 A 2 B 2 /A 1 B 2 A 2 B 1 design. The first version utilized semantically related verbs by separating hand- and face-related verbs; the other form used semantically non-related verbs. Participants 1 and 2 received treatment with the A 1 B 2 A 2 B 1 , and participants 3 and 4 received the A 1 B 1 A 2 B 2 order. Level, trend, and slope besides D statistic were analyzed for both the treated and untreated verbs. SFA was generally effective in both versions; however, greater effect sizes were obtained with semantically related verbs (28.58, 33.48, 7.07, 8.16 for the treated and 13.86, 23.09, 4.38, 4.98 for the untreated verbs in the semantically related version; 15.51, 5.72, 1.73, 6.35 for the treated and 6.35, 4.49, 1.63, 1.29 for the untreated verbs in the semantically non-related verbs). Achievement of the accuracy criterion occurred in less time for the semantically related version. Semantic-based treatments were useful with verb problems particularly when they were planned to activate allied neural assemblies. The findings of the present study uphold SFA treatment with semantically related verbs.